Optic Technician-Nurse Teams: Maximizing Efficiency And Quality In Eye Care Services (Journal of Namibian Studies : History Politics Culture, 2022)
This article examines the collaborative partnership between optic technicians and nurses in the provision of eye care services, focusing on the optimization of efficiency and quality. By leveraging their distinct skill sets and working synergistically, optic technician-nurse teams enhance patient assessment, coordinate treatment planning, and provide comprehensive support to individuals with eye-related conditions. Key aspects explored include roles and responsibilities, patient education, safety compliance, workflow efficiency, and real-life case studies. Through effective collaboration, these professionals ensure holistic care delivery and contribute significantly to improved patient outcomes.